Orthodontic retainers: are they all the same? - Telma Martins de ARAUJO; Paula Paes FERREIRA; Izabelle Alice Pinheiro Barros LISBOA; Carlos Jorge VOGEL; Carolina Ribeiro STARLING (Dental Press Journal of Orthodontics)
ABSTRACT Introduction: It is known that the stability of the results obtained with orthodontic treatment depends, in addition to the functional and aesthetic aspects, also on the adequate planning of the retention devices, the patient’s compliance with this new phase, and the physiological changes that the human body experiences over the years, throughout the craniofacial aging process. Objective: This article discusses the importance of the orthodontic retention phase and the influence of diagnosis, planning and execution of corrective treatment of malocclusions, in order to achieve the expected success. Methods: Throughout the text, different types of retainers and approaches during this phase will be presented, with the aim of ensuring the stability of the results obtained after correcting problems in the vertical, transverse and anteroposterior directions. Results: Orthodontic retainers are not all the same. The retention protocol must be performed in an individualized and planned manner, taking the initial dental positions as a reference. Conclusions: The orthodontist must inform the patient and parents about important aspects of how to maintain the occlusion achieved with orthodontic treatment. The retainers installed after the end of corrective treatment are not everlasting, they can suffer damage with use and must be replaced. Therefore, the patient must be aware of the importance of using retainers as prescribed by the orthodontist, and of returning for scheduled review appointments.